Ente trajetórias, desejos e (im)possibilidades : projetos de futuro na socioeducação de meio aberto - Koerich, Bruna Rossi (2018)
The research falls within the context of the intersection of youth, violence and temporality, especially in the case of adolescents in conflict with the law. In the last decade, the theme has gained prominence in the academic field focusing on socio-educational measures of deprivation of liberty. Despite the majority in the socio-educational system, measures carried out in an open environment are almost non-existent in the social sciences. Aiming to make these experiences visible and based on the understanding that the preponderant discourse in the guidelines of the socio-educational system is to enable futures distanced from the infraction practice, this research aims to analyze the construction of future projects of young people of the socioeducation of open means, that anchor this construction. Methodologically, we opted for an ethnographic insertion, involving observations, interviews and systematization of informal conversations with young people of an open-medium execution unit, located in the municipality of Canoas (RS, Brazil), recognized by the reduction of violence rates from of a public security policy that reinforced preventive actions. Based on Gilberto Velho's concept of possibilities field, data analysis allowed us to identify a typology of young people in the construction of their future projects, composed of two types: one related to young people with punctual insertions in infractional practices, and another with a continuous infraction trajectory. The former are characterized by projects of an "idyllic" future, without a great concern of mediation with the concrete possibilities, giving scope for a voluntaristic analysis of the process of construction of future projects. The others, characterized by recidivism and infractional practices as main forms of sociability, present projects of continuity of criminality, claiming to be the "only possibility", demonstrating a limited space for desire, contributing to a deterministic view of this process. In addition, it was possible to identify elements such as consumption and masculinity in the future projects of young people of both types and that these elements were accentuated by the experience of a temporality centered in the present, by a phenomenon of presentification.